Social Impacts of Non-Renewable Resource Development on Indigenous communities in Alaska, Greenland, and Russia - Schweitzer, Peter; Stammler, Florian; Ebsen, Cecilie; Ivanova, Aytalina; Litvina, Irina (Routledge, 2018)
In July 2009, a public meeting was held in the village of Kivalina, Alaska. It was an opportunity for community members to voice their opinions and concerns regarding the Red Dog Minex2019;s development plans and especially the mine’s new waste management permit. Community members were concerned about the mine’s impacts on their land, their health, and their community as a whole. A female community member said the following: “For the health and safety of our people and our subsistence way of life, our concerns should be heard and taken seriously, taken into consideration very seriously, for the bene?t of our future generations to come” (Public Comments 2009: 19).